2009
DOI: 10.1051/0004-6361/200811269
|View full text |Cite
|
Sign up to set email alerts
|

GALICS. II: the [ α/Fe] -mass relation in elliptical galaxies

Abstract: Aims. We test whether the mass-and σ-[α/Fe] relations in the stellar populations of early-type galaxies can be reproduced by a cosmologically motivated assembly history for spheroids. Methods. We implement a detailed treatment for the chemical evolution of H, He, O, and Fe in GalICS, a semi-analytical model for galaxy formation that successfully reproduces basic low-and high-redshift galaxy properties. We take the contribution of supernovae into account (both type Ia and II), as well as low-and intermediate-ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 82 publications
8
86
0
1
Order By: Relevance
“…It is well known that the bulge of the Milky Way is both metalrich (typically about [Fe/H] ∼ −0.3 to 0.3 with a mean of about 0) (Zoccali et al 2008) and is α enhanced (Lecureur et al 2007;Zoccali et al 2008;Ryde et al 2010). Both of these results are consistent with our simulations modulo the uncertainty in the delay times of type Ia SNe, and the mass and characteristics of preexisting bulges in the merging galaxies (see Pipino et al 2009). This general result appears to hold generally for bulges, namely they are metal-rich and α enhanced (Thomas et al 2005) and normalizing for their mass differences, very similar to early type galaxies (Thomas et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…It is well known that the bulge of the Milky Way is both metalrich (typically about [Fe/H] ∼ −0.3 to 0.3 with a mean of about 0) (Zoccali et al 2008) and is α enhanced (Lecureur et al 2007;Zoccali et al 2008;Ryde et al 2010). Both of these results are consistent with our simulations modulo the uncertainty in the delay times of type Ia SNe, and the mass and characteristics of preexisting bulges in the merging galaxies (see Pipino et al 2009). This general result appears to hold generally for bulges, namely they are metal-rich and α enhanced (Thomas et al 2005) and normalizing for their mass differences, very similar to early type galaxies (Thomas et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…This has allowed the problem of the α enhancements of elliptical galaxies to be revisited in greater details. Pipino et al (2009) showed that the inclusion of radio-mode feedback in their semi-analytic model was able to invert the slope of the galaxy stellar mass-[α/Fe] relation for massive ellipticals. The predicted slope was, however, still relatively shallow and the scatter too large, particularly for intermediate mass galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…The situation has improved significantly in recent years with detailed chemical schemes being incorporated both in hydro-dynamical simulations (Tornatore et al 2004;Scannapieco et al 2005;Wiersma et al 2009;Few et al 2012) and in semi-analytic models of galaxy formation (Nagashima et al 2005;Cora 2006;Pipino et al 2009;Arrigoni et al 2010;Benson 2012;Yates et al 2013).…”
Section: Introductionmentioning
confidence: 99%